(3GdOQQ GdaQGFO aj TQM cJGH GdbhGYO aj Gdabg ddYdGeI GdMdis - (3eMeO MSf GdeXaQs; (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3cJGH GdUdGI Ci GdeaJJMI HGdJcHjQ GdeNJJeI HGdJSdje s
(3BNQgG (B:s
(3Ke bGdJ ai GdUMjM GdePchQ hEPG GSbWJ ddSLhO hHOCJ GdYbhO hHGdQcHJjf bHd GdjOjf s
(3GdfSNI HgG MhGTs
(3HChdg agQSJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis